Experience capitalization: It's all about the how - Hampson, Karen J. (Technical Centre for Agricultural and Rural Cooperation, 2019)
Experience Capitalization is a relatively new term, but it covers similar principles to documentation or process evaluation. For me, Experience Capitalization is the HOW: in terms of “how are we doing things,” “how did we get to where we wanted to get,” and of “how did some aspects of a project work well and some not so well.”